KEPEMIMPINAN KEPALA MADRASAH DAN KINERJA GURU MADRASAH TSANAWIYAH Se-SUB RAYON 50 KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG - Muhammad Yunus; Amiruddin Siahaan; Yahfizham Yahfizham; Muhamamd Rizki Syahputra (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2021)
This study aims to find out: 1) Whether there is a positive and significant relationship with the effectiveness of madrasah head leadership on teacher performance, 2) Whether there is a positive and significant relationship with work motivation to teacher performance, 3) Is there a positive and significant relationship to the effectiveness of madrasah head leadership and work motivation together to teacher performance. This type of research is quantitative research with research location in MTs Se-Sub Rayon 50 Subdistrict Percut Sei Tuan. The population in this study was teachers in MTs Se-Sub Rayon 50 Percut Sei Tuan Subdistrict, the number of teachers 271 people actively on duty in 2020/2021. The study sample was conducted based on Kriechie Morgan's table of 153 people. The results showed that:  1) There is a positive and significant contribution between the variable effectiveness of leadership (X1) to teacher performance (Y). With the score obtained from the trend test result of 76.4% in the fairly high category, the simple correlation calculation result was obtained 0.485>0.158 at the moderate level of relationship between the leadership effectiveness variable (X1) and the teacher performance (Y). 2) There is a positive and significant contribution between the variables of teacher work motivation (X2) to teacher performance (Y). With the acquisition of the value of the trend test result of 82.4% in the fairly-high category, the simple correlation calculation result was obtained 0.790>0.158 at the high level of the relationship between the teacher's work motivation variable (X2) and the teacher's performance (Y). 3) There is a positive and significant contribution between the variable effectiveness of leadership (X1) and the motivation of teacher work (X2) together Towards teacher performance (Y) obtained R Square value (coeffesien determination) of 0.716 = 71.6%. The results of the double regression equation test also obtained the value of each variable, the magnitude of the Coefesien iregresi (β) leadership effectiveness (X1) = 0.304, the motivation of the teacher's work (X2) = 0.280, so obtained hypotheses is that there is a positive and significant contribution between the variable effectiveness of leadership (X1) and the motivation of the teacher's work (X2) to the performance of teachers (Y). So it can be interpreted if the better leadership exemplified by the head of madrasah and the motivation given to teachers in MTs Sub-Rayon 50 Percut Sei Tuan, the better the performance of teachers (Y).